Dimensional Stability of Mixed Particle Board from Merkubung (Macaranga gigantea Muell.Arg.) and Red Meranti (Shorea spp.) Wood: Kestabilan Dimensi Papan Semen Partikel Campuran Kayu Merkubung (Macaranga gigantea Muell.Arg.) dan Meranti Merah (Shorea spp.) - Jufriah; Rosita, Erly; Asih Handayani, Sri (Universitas Widya Gama Mahakam, 2025)
This study aims to determine the effect of mixing Merkubung and Red Meranti wood particles on the dimensional stability of particleboard. Particle cement boards were made using conventional methods with Merkubung and Meranti Merah particle ratios of 100:0, 0:100, and 50:50 (in %), with a target board density and thickness of 1.2 g/cm³ and 12 mm. The weight ratio of particles to cement was 1:3 with a compression pressure of 20 bar. Dimensional stability testing was carried out by testing the thickness swelling properties of the boards in accordance with ISO 8335 (1987) standards. The test results showed that the boards produced were uniform in thickness, density, and moisture content. The mixing of Merkubung and Red Meranti wood particles in equal proportions of each type of wood particle showed a significant effect. Meanwhile, Merkubung particle cement boards had no significant effect on Red Meranti particle cement boards. In terms of utilization, if particle cement boards are to be used, Merkubung wood particles cannot be mixed with Red Meranti wood particles.